2018
DOI: 10.3390/molecules23020387
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Activities of Diterpenoids Derived from Euphorbia fischeriana Steud

Abstract: Euphorbia fischeriana Steud is an essential oriental folk medicine used for healing cancer, edema and tuberculosis. Recently, its anticancer activitity has attracted more attention. A volume of research has indicated that diterpenoids are the major anticancer active constituents from this medicinal herb. In this review, we aimed to provide a summary of the promising anticancer diterpenoids from this plant; many diterpenoids mentioned in this article are newly discovered diterpenoids. According to the carbon sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 61 publications
(72 reference statements)
0
42
0
Order By: Relevance
“…The physiological (such as programmed cell destruction, physiologic involution, and regular destruction of cells) and pathological (such as anticancer drug, progressive cell death, and pathologic atrophy of organs and tissues) conditions affect the apoptosis (Wong 2011 ). Since, resisting death and avoiding apoptosis is one of the ten cancer hallmarks (Hanahan and Weinberg 2011 ), a study on the apoptosis process is applying for an important role in oncology research (Jian et al 2018 ). Figures 5 and 6 exhibit Flow cytometric evaluation and the apoptosis percentage by LUE that was quantitatively determined using PI staining.…”
Section: Resultsmentioning
confidence: 99%
“…The physiological (such as programmed cell destruction, physiologic involution, and regular destruction of cells) and pathological (such as anticancer drug, progressive cell death, and pathologic atrophy of organs and tissues) conditions affect the apoptosis (Wong 2011 ). Since, resisting death and avoiding apoptosis is one of the ten cancer hallmarks (Hanahan and Weinberg 2011 ), a study on the apoptosis process is applying for an important role in oncology research (Jian et al 2018 ). Figures 5 and 6 exhibit Flow cytometric evaluation and the apoptosis percentage by LUE that was quantitatively determined using PI staining.…”
Section: Resultsmentioning
confidence: 99%
“…However, no further studies, after 1984, were found on the investigation of the diterpenoids or the specific diterpenoids identified from FTB. As diterpenoids in other Chinese herbs may perform diverse biological activities, such as anti-cancer activity [95], anti-inflammatory activity [96] and antioxidative activity [97], further studies which focus attention on diterpenoids in FTB may be important.…”
Section: Modern Exploration Of Ftbmentioning
confidence: 99%
“…Euphorbia fischeriana is a perennial herbaceous plant of euphorbiaceae found mainly in the Northeast of China. The plant’s dried roots, named “Lang-du” in traditional Chinese medicine, have many pharmacological effects of eliminating phlegm, antitubercle, and anti-cancer [1,2,3,4,5]. The Ebracteolata Compound B, ECB (2,4-dihydroxy-6-methoxy-3-methyl acetophenone), from the acetophenone family, is of concern and in great demand in the field of medicine due to its obvious anti-tuberculosis activity [6,7,8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%